Improving Cognitive Abilities in Recognizing Colors through Science Experiments in 5-6 Year Old Children at RA Nurul Islam - Ai Nurhayati (MANDAILING GLOBAL EDUKASIA, 2025)
This class action research discusses Improving Cognitive Ability Through the Color Mixing Experiment Method in Children Aged 5-6 years at RA Nurul Islam Papayan Jatiwaras, this study is a type of classroom action research that refers to the Suharsimi Arikunto model covering four stages, namely (1) planning, (2) action, (3) observation and (4) reflection. This research consists of two cycles. The data analysis technique used in this study is qualitative data analysis. The sample in this study is 15 children of group B of RA Nurul Islam Papayan Jatiwaras in 2020/2021. The purpose of this study is to improve children's cognitive abilities through the color mixing experiment method. The data collection technique in this study uses observation sheet instruments, and documentation. From the results of observations, data was obtained that children aged 5-6 years at RA Nurul Islam Papayan Jatiwaras, in terms of cognitive ability are still lacking. The results of the study show that the application of experimental methods can improve children's cognitive abilities, as evidenced by the increase in children's scores in cycle I is 27% which is in the medium category. The score in the second cycle of 60% is in the high category. This shows that the application of experimental methods turned out to be very effective in improving children's cognitive abilities, because there was an increase in scores from cycle I to cycle II by 33%. Therefore, teachers must be able to implement the learning process in accordance with the characteristics and stages of the child's age so that learning is beneficial for children, as well as using experimental methods to improve the cognitive abilities of children aged 5-6 years.